2022
DOI: 10.1071/sh21083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bacterial vaginosis in postmenopausal women: a systematic review and meta-analysis

Abstract: Bacterial vaginosis (BV), the most common cause of vaginal discharge in women of reproductive age, is associated with considerable reproductive and gynaecological sequelae and increases the risk of acquiring sexually transmissible infections including HIV. Although we understand the burden of BV in women of reproductive age, much less is known about the burden of BV in postmenopausal women. We undertook this systematic review and meta-analysis to estimate the prevalence of BV in postmenopausal women. The elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
0
5
0
1
Order By: Relevance
“…(2) e packaging shell adopts AMC design and improves the reading speed of the label; second, since the metal layer is located at the bottom of the layer, it has good thermal conductivity at the temperature of the thermistor. (3) e button returns to the simplicity of setting [20].…”
Section: Antimetal Design Of Sensor Tagsmentioning
confidence: 99%
“…(2) e packaging shell adopts AMC design and improves the reading speed of the label; second, since the metal layer is located at the bottom of the layer, it has good thermal conductivity at the temperature of the thermistor. (3) e button returns to the simplicity of setting [20].…”
Section: Antimetal Design Of Sensor Tagsmentioning
confidence: 99%
“… 1 Among post-menopausal women, BV prevalence ranges between 2% and 57% with an overall prevalence of 16.9%, per a recent systematic review and meta-analysis including 13 English-language studies. 23 …”
Section: Epidemiologymentioning
confidence: 99%
“…A recent meta-analysis found that the prevalence of BV among postmenopausal women ranged from 2.0% to 57%, with a summary estimate of 16.9%. 44 The standard diagnostic criteria for BV are typically valid only for premenopausal individuals. 10 Amsel's criteria, commonly used in clinical practice, requires at least 3 of the 4 criteria: presence of noninflammatory vaginal discharge (typically thin, homogeneous, and non-adherent), amine odor after addition of 10% potassium hydroxide to a sample of vaginal discharge, clue cells on saline microscopy, and vaginal pH > 4.5.…”
Section: The Postmenopausal Vaginal Microbiome and Gsmmentioning
confidence: 99%
“…BV, although highly prevalent among premenopausal individuals reporting abnormal vaginal discharge, can be particularly challenging to diagnose among postmenopausal individuals. A recent meta-analysis found that the prevalence of BV among postmenopausal women ranged from 2.0% to 57%, with a summary estimate of 16.9% 44 . The standard diagnostic criteria for BV are typically valid only for premenopausal individuals 10 .…”
Section: Introductionmentioning
confidence: 99%